2021
DOI: 10.1186/s13019-021-01742-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent differences in the prognostic relevance of body composition-related variables in type A aortic dissection patients

Abstract: Background The current research is allocated to appraise the association between the parameters of body composition and findings in type A aortic dissection (TAAD) cases in diverse age groups. Methods Data from consecutive TAAD patients undergoing implantation of modified triple-branched stent-graft from January 2017 and December 2019 were prospectively collected and analyzed. A regression model of Cox proportional hazard was employed to assess cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Moreover, 2 independent retrospective cohort studies in Japan [ 7 , 8 ] and 1 in Italy [ 22 ] identified obesity (BMI ≥ 30.0) as a risk factor of in-hospital mortality in ATAAD patients who underwent surgical repairs (OR = 3.00, 95% CI: 1.40–6.20, OR = 3.16, 95% CI: 1.48–6.74, and OR = 2.14, 95% CI: 1.22–3.78). However, a retrospective cohort study conducted in Germany [ 9 ] and 2 in China [ 10 , 24 ] found no associations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 2 independent retrospective cohort studies in Japan [ 7 , 8 ] and 1 in Italy [ 22 ] identified obesity (BMI ≥ 30.0) as a risk factor of in-hospital mortality in ATAAD patients who underwent surgical repairs (OR = 3.00, 95% CI: 1.40–6.20, OR = 3.16, 95% CI: 1.48–6.74, and OR = 2.14, 95% CI: 1.22–3.78). However, a retrospective cohort study conducted in Germany [ 9 ] and 2 in China [ 10 , 24 ] found no associations.…”
Section: Resultsmentioning
confidence: 99%